Potensi Spaghettini Komposit Semolina Durum-Pati Ganyong dalam Pembentukan Short Chain Fatty Acid dan Asam Laktat pada Fermentasi Menggunakan Mikroflora Feses Manusia - Stefani Amanda Harmani; Haryadi Haryadi; Muhammad Nur Cahyanto; Yudi Pranoto (agriTECH, 2016)
Nowadays people have started considering the health beneficial value in selecting food. Government’s demand for utilization of local food and food diversification is also increasing. Considering those reasons, the objective of this study was to create a way of food diversification using local ingredient which has physiological benefits for human health. Resistant starch can improve human colonic health through fermentation by colonic microflora to produce Short Chain Fatty Acid (SCFA) and lactic acid. This research was conducted by combining canna starch with semolina durum into a composite flour for spaghettini production. Various type of canna tuber and canna starch proportion were used in the composite flour. Semolina durum contained higher resistant starch (20%) than red canna starch (17.7%) and green canna starch (15.4%). Combination of durum and red canna starch-based spaghettini produced higher amount of resistant starch, SCFA, and lactic acid than combination of durum and green canna starch- based spaghettini. Durumcanna based spaghettini had the ability to produce SCFA and lactic acid during in vitro fermentation using human colonic microflora although the concentration was lower than those of only durum spaghettini.ABSTRAKKriteria pemilihan makanan oleh masyarakat kini mulai mempertimbangkan nilai kesehatan dari suatu makanan. Sementara, permintaan pemerintah untuk pemanfaatan bahan baku lokal dan diversifikasi pangan pokok pun semakin meningkat. Oleh karena itu, penelitian ini dilaksanakan untuk mewujudkan penganekaragaman pangan berbasis tepung komposit dari bahan baku lokal yang memiliki nilai fungsional untuk kesehatan kolon. Resistant Starch (RS) dapat meningkatkan kesehatan kolon melalui hasil fermentasinya oleh bakteri usus besar yang berupa Short Chain Fatty Acid (SCFA) dan asam laktat. Penelitian dilakukan dengan mengkombinasikan pati ganyong dan semolina sebagai bahan dasar pembuatan spaghettini. Variasi yang digunakan ialah variasi jenis umbi ganyong serta variasi jumlah pati ganyong dalam tepung komposit. Kadar RS semolina (20%) lebih tinggi daripada kadar RS pati ganyong ungu (17,7%) dan pati ganyong hijau (15,4%). Kadar RS, SCFA, dan asam laktat yang dihasilkan spaghettini durum-pati ganyong ungu lebih besar daripada spaghettini durum-pati ganyong hijau. Spaghettini komposit durum-pati ganyong mampu menghasilkan SCFA dan asam laktat melalui fermentasi in vitro menggunakan mikroflora feses manusia dengan kadar yang lebih rendah daripada spaghettini 100% durum.